The Management of Independent Educational-Cognitive Activities of Future Specialists in the Process of Vocational Training - Maksimov, Ilya N.; Faleeva, Liya V.; Pavlova, Oksana A.; Fassakhova, Guzel R.; Islamova, Liliya R.; Timonina, Alexandra A.; Kurdyumov, Vladimir I.; Tokareva, Evgenia Y. (International Review of Management and Marketing, 2016)
The development of a modern economy fundamentally changes the requirements for professional staff. Specialists who not only have an excellent command of their profession, are actively involved in the improvement of production, but also seek to improve their skills, master related professions are still in demand. This leads to new targets of professional training of future specialists, including the formation of readiness for independent educational cognitive activities. The purpose of this paper is to define the peculiarities of the management of independent educational-cognitive activities of future specialists in the process of vocational training. The leading approaches to the study are the system approach that allows considering of the management of independent educational-cognitive activities of future specialists as a continuous purposeful process, and an integrative approach allowing to organize the process of formation of future specialists’ readiness for independent educational-cognitive activities on different logical grounds. The article reveals the methods and functions of self-educational-cognitive activities of future specialists; defines the content of future specialists’ readiness for independent educational-cognitive activities; presents the mechanism and pedagogical conditions of formation of future specialists’ readiness for independent educational cognitive activities in the process of vocational training. The paper submissions may be useful for scientific and pedagogical workers of educational institutions; employees of the centers of advanced training and retraining of personnel in the selection and structuring of the content for the training of scientific and pedagogical staff. Keywords: independent educational-cognitive activities, long life education, management of vocational training. JEL Classifications: I21, I25, I28